2022
DOI: 10.21744/lingcure.v6ns3.2107
|View full text |Cite
|
Sign up to set email alerts
|

Commodification of media in helping public relations performance in the regional development sector in Indonesia

Abstract: Indonesia is referred to as a multicultural country, so the context of the multicultural country that is built is based on ethnicity, race, religion, groups and not customary groups where the placement of customs is part of the process of formulating public policies. This means that the context of life in the Indonesian state is multikulepresion or a country consisting of various kinds of differences. Therefore, to build good relations, it is necessary to build multicultural communication, especially in any me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In addition, these two experts also stated that the path that connects policies and works performance is separated by a number of interrelated factors, such as 1) the size and objectives of the policy, 2) the sources of the policy, 3) the characteristics of the agency or the implementing institution, 4) communication between the organizations involved and the implementation activities, 5) attitudes of implementers and 6) economic, social and political environment. Based on the explanation above, it can be concluded that the concept of policy socialization leads to a dynamic activity that is responsible for implementing the program and setting the goals of the policy so that it will eventually produce a result that is in accordance with the goals or objectives of the policy itself (Anike et al, 2017;Diegtiar et al, 2021;Larisu & Mona, 2022;Vavrus & Bartlett, 2006).…”
Section: Concept Of Public Policymentioning
confidence: 99%
“…In addition, these two experts also stated that the path that connects policies and works performance is separated by a number of interrelated factors, such as 1) the size and objectives of the policy, 2) the sources of the policy, 3) the characteristics of the agency or the implementing institution, 4) communication between the organizations involved and the implementation activities, 5) attitudes of implementers and 6) economic, social and political environment. Based on the explanation above, it can be concluded that the concept of policy socialization leads to a dynamic activity that is responsible for implementing the program and setting the goals of the policy so that it will eventually produce a result that is in accordance with the goals or objectives of the policy itself (Anike et al, 2017;Diegtiar et al, 2021;Larisu & Mona, 2022;Vavrus & Bartlett, 2006).…”
Section: Concept Of Public Policymentioning
confidence: 99%
“…In addition, these two experts also stated that the path that connects policies and works performance is separated by a number of interrelated factors, such as 1) the size and objectives of the policy, 2) the sources of the policy, 3) the characteristics of the agency or the implementing institution, 4) communication between the organizations involved and the implementation activities, 5) attitudes of implementers and 6) economic, social and political environment. Based on the explanation above, it can be concluded that the concept of policy socialization leads to a dynamic activity that is responsible for implementing the program and setting the goals of the policy so that it will eventually produce a result that is in accordance with the goals or objectives of the policy itself (Anike et al, 2017;Diegtiar et al, 2021;Larisu & Mona, 2022;Vavrus & Bartlett, 2006).…”
Section: Concept Of Public Policymentioning
confidence: 99%